2017
DOI: 10.1016/j.jaci.2016.12.967
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide interaction study of dust mite allergen on lung function in children with asthma

Abstract: Background Childhood asthma is likely the result of gene-by-environment (G×E) interactions. Dust mite is a known risk factor for asthma morbidity. Yet, there have been no genome-wide G×E studies of dust mite allergen on asthma-related phenotypes. Objective To identify genetic variants whose effects on lung function in children with asthma are modified by level of dust mite allergen exposure. Methods A genome-wide interaction analysis of dust mite allergen level and lung function was performed in a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
0
22
1
Order By: Relevance
“…Up to now, few GWIS have been conducted for asthma‐related phenotypes and only one reported a genome‐wide significant result for a rare variant (MAF = 1.5%) interacting with dust mite exposure on lung function . One of the difficulties in GWIS is the need of large scale studies to detect significant interaction, which in turn might be affected by heterogeneity in study designs, outcome and exposure definitions of the participating studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Up to now, few GWIS have been conducted for asthma‐related phenotypes and only one reported a genome‐wide significant result for a rare variant (MAF = 1.5%) interacting with dust mite exposure on lung function . One of the difficulties in GWIS is the need of large scale studies to detect significant interaction, which in turn might be affected by heterogeneity in study designs, outcome and exposure definitions of the participating studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Novel insights into how these responses occur following individual and combined exposures, and their associated health impacts, continue to emerge. Genetic polymorphisms also interact with many other environmental stressors to generate asthma phenotypes such as decreased lung function, adult‐onset asthma, or the severe asthma phenotype . Air pollution also induces transcriptomic, epigenomic, and metabolomic responses …”
Section: Framing the Issuementioning
confidence: 99%
“…, and this past year, several studies expanded our knowledge of the influence of early-life allergen exposure on asthma risk and demonstrated interactions between these indoor allergens and genetic polymorphisms. 49,[53][54][55][56] These gene-environment interactions could act through epigenetic or nonepigenetic mechanisms. In addition, studies demonstrated links between genetic signatures and asthma phenotypes related to steroid responsiveness, adult-onset asthma, and total IgE levels.…”
Section: Cellular Mechanisms In Asthmatic Patientsmentioning
confidence: 99%
“…The role played by the environment in shaping the development and exacerbation of asthma is examined as well (Fig 3). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] We conclude with a section on health literacy, a critical component for successfully treating asthma, and other related advances.…”
mentioning
confidence: 99%